2022
DOI: 10.2147/jhl.s376089
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Experiences of Internal Medicine Residents: A Needs Assessment for Leadership Curricula

Abstract: Purpose Leadership development during medical training is critical. Accrediting bodies strongly recommend and residents desire leadership training. However, limited needs assessment data exist regarding trainee perceptions of and experiences with leadership training. Our objective is to describe residents’ perceptions of leadership and desires for leadership training with the goal of informing effective curricular development. Patients and Methods In 2019 a trained qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…However, the residents showed their struggle and variations in developing leadership skills relying on their learning environment only. A recent study among internal medicine residents showed the same struggle that might provide inconsistent leadership background, which does not ensure equivalent development of leadership skills [ 17 ]. To support the development of leadership skills, leadership skills must become a standard part of medical training at all levels and in all specialties [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the residents showed their struggle and variations in developing leadership skills relying on their learning environment only. A recent study among internal medicine residents showed the same struggle that might provide inconsistent leadership background, which does not ensure equivalent development of leadership skills [ 17 ]. To support the development of leadership skills, leadership skills must become a standard part of medical training at all levels and in all specialties [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an expanding interest in leadership development programs among physicians, and formal training is currently available in 65% of academic health centers in the United States of America [ 1 ]. The enthusiasm for physician leadership training among residents is increasing [ 2 ], and the necessity to educate them on such a topic is evident [ 3 ], as residents are expected to participate in multidisciplinary rounds, lead a team, be active advocates of patient safety, and share the responsibilities of educating junior residents and students. The most recent Accreditation Council of Graduate Medical Education (ACGME) 2.0 Milestones [ 4 ] highlight the importance of advancing resident performance in leadership in most competency areas; thus, early exposure to healthcare administration and leadership is paramount to the contemporary internal medicine (IM) trainee.…”
Section: Editorialmentioning
confidence: 99%
“…Existing evidence about the efficacy of leadership programs for graduate medical trainees [ 5 ] is sparse and conflicting. There is a significant misconception among trainees who appreciate that leadership development is primarily about enhancing individual knowledge and skills in the hierarchical and archaic model of leadership [ 2 ] at the level of a microsystem. The existent leadership programs have not adopted contemporary views of leadership as a collective practice, and there is little evidence to support their efficacy.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations